Петр Аркадьевич Столыпин как воплощение российского менталитета - Сайгушкина, Т.П. (Культура народов Причерноморья, 2013)
В статье рассматривается личность министра внутренних дел и председателя Совета
министров Российской империи П.А. Столыпина в применении к понятию «интеллигентность».
Сравниваются различные определения этого термина. Изучаются особенности значения слов
«интеллигенция», «интеллигент», «интеллигентность» в отечественной культуре. Предполагается,
что истоки этих особенностей – в православной этике и культуре. На основе хронологического метода
петербургского культуролога М.С. Кагана предполагается, к какому типу интеллигента относится
Петр Аркадьевич Столыпин. У статті розглядається особистість міністра внутрішніх справ і голови Ради міністрів
Російської імперії П.А. Столипіна в застосуванні до поняття «інтелігентність». Порівнюються різні
визначення цього терміна. Вивчаються особливості значення слів «інтелігенція», «інтелігент»,
«інтелігентність» у вітчизняній культурі. Передбачається, що витоки цих особливостей - у
православній етиці та культурі. На основі хронологічного методу петербурзького культуролога
М.С. Кагана передбачається, до якого типу інтелігента відноситься Петро Аркадійович Столипін. The article studies the personality of the statesman, the Minister of Internal Affairs and the Chairman
of the Council of Ministers of the Russian Empire, Pyotr Stolypin (1862-1911) in the light of the concept of
“intelligence” on the example of his biography: public and state activities, human appearance, personal and
family life. The personality of Pyotr Arkadyevich Stolypin with the beginning of perestroika and changes in the
political and economic system calls for an attention of historians, economists, politicians, and sociologists. It is
interesting to study the life and activity of this very person with moral and philosophic point of view. The various
definitions of the term “the intelligentsia” are compared with each other. The meanings of the words “the
intelligentsia”, “intellectual”, and “intelligence” in the Russian culture are carefully studied. It is assumed that
the origins of these features are in the Orthodox ethics and culture. The St. Petersburg culture expert
M.S. Kagan has determined several types of the Russian intellectual (noble intellectual, intellectual-commoner,
and proletarian intellectual). P.A. Stolypin’s quotes from his speeches in the State Duma gave the opportunity to
include Pyotr Arkadyevich to one or another type of the intellectual. The personality of Stolypin correlated with
other examples of Russian intellectuals. It is possible to conclude that Stolypin is an example of a noble family of
intellectuals which proved his selfless service to the country and people.